Investigating the influence of freezing rate and frozen storage conditions on a model sponge cake using synchrotron X-rays micro-computed tomography. (December 2022) - Zennoune, Amira; Latil, Pierre; Flin, Frederic; Perrin, Jonathan; Weitkamp, Timm; Scheel, Mario; Geindreau, Christian; Benkhelifa, Hayat; Ndoye, Fatou-Toutie
Graphical abstract: Highlights: Microstructure studied according to freezing rates and frozen storage conditions. Thermostated cell coupled to synchrotron beamline for frozen microstructure analysis. Ice crystals mainly located at the pore surface for slow freezing rate. Local redistribution of water occurred in fast frozen samples during storage. Water migration towards pores favored by fluctuating storage temperatures. Abstract: Synchrotron X-rays micro-computed tomography was applied to visualize and quantify 3D ice crystal changes into a model sponge cake after freezing and subsequent frozen storage. Model sponge cake samples were submitted to two different freezing rates (fast: 17.2 °C min −1 and slow: 0.3 °C min −1 ), then stored at constant and fluctuating temperatures over a two weeks period. 3D images were acquired at frozen state thanks to a thermostated cell (CellStat) and processed using a grey level based segmentation method. Image analysis revealed that the ice volume fraction is conserved during storage but ice crystal size and location change whatever the freezing rate and the storage conditions. Maximum local thicknesses increase both inside (from 20 µm to 50 µm) and outside (from 47 µm to 70 µm) the matrix during the fourteen days storage period. Both specific surface areas between starch and ice (SSAice/starch ) and between air and ice (SSAair/ice ) also evolve with storage duration: SSAice/starch decreases up to − 30 % while SSAair/ice increases up to + 13 % depending on the freezing rates and the storage conditions. These results highlighted that, during storage, ice crystals evolve according to two different mechanisms depending on the freezing rate: fast freezing leads to a local redistribution of water both within the starch matrix and within the pores, while slow freezing results in both local redistribution within the starch matrix and water migration towards the pores. In addition, stable storage temperatures favor local water redistribution whereas water migration from the starch matrix towards the pores was greater in the case of fluctuating storage temperatures. This study shows that freezing and frozen storage conditions have a synergistic effect on the microstructure evolution of sponge cake due to recrystallization phenomena.